PENGARUH JUMLAH DAN SUDUT PEMASANGAN SUDU TERHADAP DAYA TURBIN ANGIN SAVONIUS - Purwoko; Santoso (Jurnal Teknik Ilmu dan Aplikasi, 2020)
The problem in Energy conservation is finding new opportunities for high-efficiency energy generation including wind power generating machines. This study aims to determine the effect of the number and curv angle of blade mounting on the output power of a Savonius type wind turbine. This low speed wind turbine is intended to get energy at the top of a multi-storey building in an urban area. Tests were carried out on a laboratory scale, using savonius wind turbines with a diameter of 400 mm and a height of 500 mm. The driving wind speed of the turbine is set between 1.5 to 8.5 m / s. While the number of blades used is 2 types, namely rotor with three blades and rotor with 4 blades, each of which is tested on 3 different types of curv angle blade. The investigation results are expected to show that the wind tubing from each experiment will give different characteristics. The results showed that there was an increase in efficiency in the savonius turbine with blades. The highest rotation and power occur when the turbine uses 2 blades and -50 curv angle of blade mounting.